PENGARUH KEDISIPLINAN TERHADAP TINGKAT PRESTASI BELAJAR SISWA DI SDN MURTAJIH PAMEKASAN - Atnawi Atnawi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
Education as one of the most important sectors in national development, is made and developed the main one that is made as much as possible in improving the quality of life of Indonesian people, where faith and piety for Allah SWT become a source of motivation for life in every field. Education also sees one aspect that has a major role in shaping future generations. With education that can be expected to produce quality human beings who are responsible and able to win the future. Higher education needs to be done, so education must be implemented and approved by formal education schools is the place that makes it easier forsomeone to increase knowledge, and the easiest to foster young people carried out by the government and society. Learning with discipline that can avoid feeling lazy and arouse students' enthusiasm in learning, which in turn can improve student learning abilities.